2021
DOI: 10.3389/fonc.2021.711171
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Value of MicroRNAs in Metastasis and Recurrence of Head and Neck Squamous Cell Carcinoma: A Systematic Review and Meta-Analysis

Abstract: MicroRNAs have been proven to make remarkable differences in the clinical behaviors of head and neck squamous cell carcinoma (HNSCC). This study aims to systematically analyze whether differential expression levels of microRNAs are related to recurrence or metastasis in patients with HNSCC. A comprehensive search of the PubMed, EMBASE, and CENTRAL was conducted up to July 24th, 2021. Data were collected and combined from studies reporting recurrence-free survival (RFS) of HNSCC patients with high microRNA expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Mature miRNA binds to the target gene mRNA through nucleic acid sequence complementarity in order to inhibit the translation of the target gene mRNA or degrade it. Its function involves cell differentiation, proliferation, apoptosis, invasion, and metastasis ( Qiu et al, 2021 ). Some scholars have studied the distribution and biological function of miRNA in mammals and found that it is involved in almost all life processes of organisms, including development events, epidermal morphogenesis, cell differentiation, enzyme activity, hormone secretion, and other regulation processes ( Corrêa et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mature miRNA binds to the target gene mRNA through nucleic acid sequence complementarity in order to inhibit the translation of the target gene mRNA or degrade it. Its function involves cell differentiation, proliferation, apoptosis, invasion, and metastasis ( Qiu et al, 2021 ). Some scholars have studied the distribution and biological function of miRNA in mammals and found that it is involved in almost all life processes of organisms, including development events, epidermal morphogenesis, cell differentiation, enzyme activity, hormone secretion, and other regulation processes ( Corrêa et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the last 10 years, it has been shown that microRNAs play an important role in the development of HNSCC cancer and its spread ( Qiu et al, 2021 ; Shiah et al, 2021 ; Yang et al, 2019 ; Yu et al, 2019 ). This makes them good candidates for biomarkers that can predict the biological activity of HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…A number of novel prognostic biomarkers for HNSCC have been explored (7)(8)(9). However, none of these has been recommended for routine clinical testing.…”
Section: Introductionmentioning
confidence: 99%